2016
DOI: 10.1200/jco.2016.68.0702
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus for the Treatment of Advanced Pancreatic Neuroendocrine Tumors: Overall Survival and Circulating Biomarkers From the Randomized, Phase III RADIANT-3 Study

Abstract: Purpose Everolimus improved median progression-free survival by 6.4 months in patients with advanced pancreatic neuroendocrine tumors (NET) compared with placebo in the RADIANT-3 study. Here, we present the final overall survival (OS) data and data on the impact of biomarkers on OS from the RADIANT-3 study. Methods Patients with advanced, progressive, low- or intermediate-grade pancreatic NET were randomly assigned to everolimus 10 mg/day (n = 207) or placebo (n = 203). Crossover from placebo to open-label eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
202
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(209 citation statements)
references
References 20 publications
5
202
2
Order By: Relevance
“…In addition, elevated baseline CgA and NSE levels were associated with shorter PFS and OS with everolimus treatment[141]. Similarly, sub-analysis of RADIANT-3 trial also showed that high baseline CgA, NSE, placental growth factor (PIGF) or soluble vascular endothelial growth factor receptor 1 (sVEGFR1) levels were associated with poor OS[65], however, baseline CgA levels were not predictive for everolimus treatment effect on OS in the RADIANT-2 trial[59]. Another study genotyped the fibroblast growth factor receptor 4 (FGFR4) using DNA isolated from tissue or blood in panNETs, and found that patients homozygous for FGFR-G388 demonstrated greater tumor shrinkage with everolimus treatment than those harboring only one FGFR4-R388 allele[142].…”
Section: Markers Predicting Efficacy Of Everolimusmentioning
confidence: 99%
“…In addition, elevated baseline CgA and NSE levels were associated with shorter PFS and OS with everolimus treatment[141]. Similarly, sub-analysis of RADIANT-3 trial also showed that high baseline CgA, NSE, placental growth factor (PIGF) or soluble vascular endothelial growth factor receptor 1 (sVEGFR1) levels were associated with poor OS[65], however, baseline CgA levels were not predictive for everolimus treatment effect on OS in the RADIANT-2 trial[59]. Another study genotyped the fibroblast growth factor receptor 4 (FGFR4) using DNA isolated from tissue or blood in panNETs, and found that patients homozygous for FGFR-G388 demonstrated greater tumor shrinkage with everolimus treatment than those harboring only one FGFR4-R388 allele[142].…”
Section: Markers Predicting Efficacy Of Everolimusmentioning
confidence: 99%
“…Noteworthy, in none of these trials a significant OS benefit was demonstrated. [8][9][10][11][12][13][14][15] Conclusion: To date, published trials are comparable in design and efficacy, and the corresponding MCBS-FT score of 2-3 is consistent with the moderate clinical benefit seen while treating patients with advanced or metastatic NET. The fact that all trials rated equally in quite similar clinical settings reflects however one difficulty of the scale in its current version: as only one trial may be considered at once (except for meta-analyses), there is no additional information for optimal sequencing of treatment options added by the ESMO-MCBS scoring system; this has also previously been discussed for colorectal cancer and renal cell cancer in our pilot analysis.…”
Section: Results Neuroendocrine Tumoursmentioning
confidence: 53%
“…[8][9][10][11][12][13][14][15] Assessment of ESMO-MCBS scores for advanced NET revealed comparable results in all available data (all trials placebo controlled). The CLARINET and the PROMID trial represent two proof of principle studies demonstrating for the first time direct antiproliferative effects of somatostatin analogues for advanced midgut and pancreatic NET irrespective of progression status.…”
Section: Results Neuroendocrine Tumoursmentioning
confidence: 74%
See 1 more Smart Citation
“…The oral mTOR inhibitor everolimus has been extensively studied in GEP-NETs. A randomized phase III study evaluating the efficacy of everolimus in advanced pNENs had been demonstrated to prolong PFS duration in patients with advanced-stage pNENs when compared with placebo (67). As a result of the significant improvement in PFS, everolimus was approved by the FDA for treatment of patients with advanced pancreatic NETs.…”
Section: Mtor Inhibitorsmentioning
confidence: 99%